La géohistoire du royaume d’Abomey (1645-1894), dans le récit national et dans la formation territoriale du Bénin contemporain - Jean Rieucau (M@ppemonde)
The geohistory of the kingdom of Abomey, based on the ethnic group, the language of the Fon and the voodoo religion, covers three and a half centuries (1645 to 1894). This small warlike nation-state, slaver, partner of European slave traders (French, Portuguese, English, Danish), lost its sovereignty at the end of the 19th century, by integrating the French colony of Dahomey. It is home to one of the most brilliant civilizations of sub-Saharan Africa, which founded the cultural soft power (restitutions of African art, memory of slavery, construction of museums, cultural tourism) of the current Republic of Benin.